2022
DOI: 10.30574/gscbps.2022.18.1.0371
|View full text |Cite
|
Sign up to set email alerts
|

Eclipta prostrata (L.) L. (uses and bioactivities)

Abstract: Eclipta prostrata has been long used by humans as traditional medicine and hair fertilizer. This study aims to explain the relationship between utilization and bioactivity of E. prostrata. The method used is a literature review of articles published online on Google Scholar using the keywords E. prostrata, uses E. prostrata, and bioactivity of E. prostrata. Ethnobotanically, E. prostrata is used to treat liver disorders, liver tonic, respiratory disorders (asthma, cough), hepatitis, snake venom poisoning, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A study conducted on rats showed that treatment with extract of this plant significantly reduced venom's effects (hepatoprotective properties) and increased the rats' survival rate 12 .…”
Section: Asteraceae Flavonoids Wedelolactone Ecliptofolinmentioning
confidence: 99%
“…A study conducted on rats showed that treatment with extract of this plant significantly reduced venom's effects (hepatoprotective properties) and increased the rats' survival rate 12 .…”
Section: Asteraceae Flavonoids Wedelolactone Ecliptofolinmentioning
confidence: 99%
“…E. prostrata (syn. Eclipta alba (L.) Hassak) is an essential medicinal plant in the tropical and subtropical regions ( Rahman et al, 2011 ; Feng et al, 2019 ; Sanyal et al, 2022 ; Silalahi, 2022 ). A whole-plant methanol extract of E. prostrata was tested for its in vitro α-amylase inhibitory activities.…”
Section: Asteraceae: Undisputable Metabolites Of Interest In Dmmentioning
confidence: 99%
“…One individual E. prostrata can make 17,000 seeds in one season [39] [40] despite having low to moderate competitiveness [41]. This weed contains secondary metabolites, now widely used in health and care [43].…”
Section: Weed Propagules Of Rice Before Tillagementioning
confidence: 99%